Mesozoic–Cenozoic sedimentary rock records and applications for provenance of sediments and affiliation of the Simao Terrane, SW China. Issue 18 (12th December 2019) - Yang, Lifei; Wang, Changming; Bagas, Leon; Du, Bin; Zhang, Duan
ABSTRACT: As the north part of Simao Terrane, Lanping Basin is located between the Sanjiang Tethys Orogen (STO) and Yangtze Block, also the junction zone between the Gondwanaland and Cathaysian old land (Pan Huaxia mainland), which includes Yangtze and Cathaysian Blocks. The aim of this study is to decipher the provenance of the sedimentary units in the Lanping Basin and affiliation of Simao Terrane by the U-Pb ages, Hf isotope of detrital zircons and whole-rock geochemistry. The whole-rock geochemistry and the mineral composition indicate that most of the Triassic–Paleocene sedimentary rocks are derived from the upper crust and exhibit recycled orogen features. The detrital zircon U-Pb ages from the North Simao Terrane are consistent with the magmatic events during Early Neoproterozoic and Permian in the Western Yangtze Block. And the detrital zircons ages from North Simao Terrane show same distribution features as the Permian–Triassic magmatic rocks, which are distributed in the Simao Terrane and along major sutures. These comparisons suggest that the clastic sediments in Lanping Basin (North Simao Terrane) are derived from Early Neoproterozoic and Permian magmatic rocks from Western Yangtze Block, Permian–Triassic magmatic rocks from Simao Terrane, along Jinshajiang, Garz-Litang and Ailaoshan Sutures. The comparison of the detrital zircon age distributions shows that Simao Terrane and Yangtze Block exhibited similarity tectonic setting in the evolution history, especially during Paleoproterozoic–Late Paleozoic. This suggests that the Simao Terrane is part of Cathaysian old land, although Simao Terrane was separated from Yangtze Block for short period during Early Paleozoic. Besides, the Hf mapping, stratigraphic succession, paleogeography and paleomagnetism in SW China support that Simao Terrane has a Cathaysian old land-affinity, rather than one involving Gondwanaland.